Biocompatibility of nanosilver-coated orthodontic brackets: an in vivo study - Gamze Metin-Gürsoy; Lale Taner; Emre Barış (SpringerOpen, 2016)
Abstract Background Nanosilver particles of which antibacterial and antifungal properties have been shown in various in vitro and in vivo studies are used in many medical and dental fields for the prevention of infection. In this study, it is intended to evaluate the biocompatibility of nanosilver-coated brackets. Methods Nanosilver coating process was applied to the standard orthodontic brackets by a physical vapor deposition system. Brackets were coated with nanosilver particles of 1 μ thickness. A total of 12 Wistar Albino rats were included in the study (six) and control (six) groups. For the study and control groups, four nanosilver-coated and four standard brackets were aseptically implanted subcutaneously in the dorsal region of each rat. The brackets were removed with the surrounding tissues on days 7, 14, 30, and 60. The specimens were evaluated for inflammatory response. Results No significant difference was found in terms of tissue reaction between the study and control groups. On day 7, randomly distributed brown-black granules were seen in the granulation tissue adjacent to the bracket in the study group. These foreign particles continued along the bracket cavity in a few samples, but the inflammatory response was insignificant between the groups. Mast cell count was found to be significantly smaller only on day 7 in the study group than in the control group. Conclusions Nanosilver-coated orthodontic brackets were found to be similar with the standard type concerning inflammation. Further researches are needed with regard to the assessment of the brown-black granules, especially on the deposition of the vessel walls.